Pengaruh Kompensasi Finansial dan Kompensasi Non Finansial terhadap Kepuasan Kerja Karyawan Bagian Produksi Pabrik Roti Sarinda Kota Ambon - Mohamad Amin (Akutansi Bisnis & Manajemen ( ABM ), 2014)
The purpose of this study were: (1) To analyze whether there are compensating factors influence among other financial and non financial compensation to employee satisfaction at the Bread Factory Sarinda - Ambon; and (2) To analyze the variables between the compensation factors include financial and non financial compensation which the dominant influence on job satisfaction of employees at the Bread Factory Sarinda - Ambon. This study uses survey research is research that takes a sample from a population that existed at the Bread Factory Sarinda in Ambon and the use of questionnaires as the primary means of data collection, while the type of research is explanatory research or studies that examined the causal relationships between variables through hypothesis testing. In this study describes the influence of compensation factors on job satisfaction Sarinda Bread Factory - Ambon. The population is an employee were 30 peoples. Analytical techniques used in this study is the multiple linear regression analysis. Based on the results of research conducted it can be concluded that: (1) Financial compensation and non-financial compensation and a significant positive effect on job satisfaction, higher financial compensation with non-financial compensation of employees will lead to increased employee satisfaction Sarinda Bread Factory in the city of Ambon; (2) It is known that the independent variable X1 (financial compensation) are independent variables that have a dominant influence on job satisfaction compared with other independent variables; and (3) The magnitude of the coefficient of determination (R2) = 0936 and after adjusting to Ajusted R Square = 0932 shows that the financial compensation and non-financial compensation together provide contribution / donation of 93,2% to changes in job satisfaction while the remaining 6.8%.